Analisis Asam Lemak Omega-3 dari Minyak Kepala Ikan Sunglir (Elagatis bipinnulata) melalui Esterifikasi Enzimatik - Handayani, Sri Seno; Gunawan, Erin Ryantin; Kurniawati, Lely; Murniati, Murniati; Budiarto, Lalu Haris (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
Omega-3 fatty acid is the essential fatty acid and important for human health. Omega-3 fatty acid is also really neededby pregnant and lactating mothers and also children to prevent the malnutrition. Omega-3 fatty acid is also reallyneeded by pregnant and lactating mothers, and children to prevent the malnutrition. The omega-3 fatty acid is commonlyfound in some fish like salmon, tuna, hering, and mackarel. However, those fish are expensive, so alternativesources relatively cheaper fish. One of fish that is low in price and high in production in Nusa Tenggara Barat is Sunglir(Elagatis bipinnulata ). The purpose of this research was to determine free fatty acids content, type of omega-3 fattyacids, and their compositions in head fish oil. Head of sunglir fish was used as a sample because the head was usuallynot consumed. Sunglir fish was obtained from the Ampenan beach (NTB) with a size of 20–30 cm. The extraction methodused in this study was soxhletation with n-hexane solvent and analyzed with Gas Chromatografi (GC), acid ethyl estersfrom the esterification enzymatic of fish oil. Result revealed that the fish oil contained 84% free fatty acid and 0.85%linolenic acid (ALA), 2.80% eicosatrienoic acid (ETA), 0.73% eicosapentaenoic acid (EPA) and 2.41% docosahexaenoicacid (DHA). Saponification and iodine number of head fish oil is 248.24 mg KOH/g oil and 227.16 g Iod/100 g oil.